2012
DOI: 10.1016/j.jcrc.2012.02.002
|View full text |Cite
|
Sign up to set email alerts
|

African American race, obesity, and blood product transfusion are risk factors for acute kidney injury in critically ill trauma patients

Abstract: Purpose Acute kidney injury (AKI) is a common source of morbidity after trauma. We sought to determine novel risk factors for AKI, by Acute Kidney Injury Network (AKIN) criteria, in critically ill trauma patients. Materials and Methods Prospective cohort study of 400 patients admitted to the ICU of a level one trauma center, followed for development of AKI over five days. Results AKI developed in 147/400 (36.8%) patients. In multivariable regression analysis, independent risk factors for AKI included Afric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
81
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 27 publications
8
81
2
1
Order By: Relevance
“…There are several potential explanations for this finding. African descent is an independent risk factor for AKI (29,45). It is possible that, in individuals of African descent, any protective effects of blood type O are overwhelmed by other mechanisms that increase their AKI risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several potential explanations for this finding. African descent is an independent risk factor for AKI (29,45). It is possible that, in individuals of African descent, any protective effects of blood type O are overwhelmed by other mechanisms that increase their AKI risk.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed inclusion and exclusion criteria have been previously described (29,30). Patients were included if they had an injury severity score .15 (31).…”
Section: Trauma Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, those who received PRBCs were roughly 3 times more likely to experience acute respiratory distress syndrome (OR, 2.5; 95% CI, 1.6-3.3) and almost twice as likely to die (OR, 1.7; 95% CI, 1.4-1.9). Other investigators found similar associations between transfusion of PRBCs and adverse clinical outcomes such as transfusion-related acute lung injury, 25 acute kidney injury, 26 and thromboembolic events. 27 However, many of these studies were retrospective and observational; thus, the outcomes may have been due to other factors.…”
Section: Transfusion Of Blood Components and Potential Consequencesmentioning
confidence: 61%
“…Shashaty et al published risk factors for the development of AKI included obesity, being of African-American descent, and blood products given. 17 Obese patients after trauma are at higher risk for deep venous thrombosis (DVT) and possible pulmonary embolism (PE), which could lead to an increase chance of mortality. Patients following trauma have shown to be at a hypercoagulable state.…”
Section: The Effect Of Bmi On Recovery Time In Trauma Injurymentioning
confidence: 99%